ANALYSIS OF IMPLEMENTATION OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM (OHSMS) AT HOSPITAL X PEKANBARU AT 2020 - Risanova Yurnan (Jurnal Kesehatan Masyarakat Andalas, 2020)
OHSMS is applied for risk control related to work activities. OHSMS in RS X such as OHS policy, planning, implementation, monitoring and evaluation of OHS, as well as management review has not run optimally.The purpose was to analyze the application of OHSMS at Hospital X. This is qualitative descriptive research with 6 informants with purposive sampling. Collecting data by in-depth interviews, observation, document review. The results, only 2 members in OHS Unit with an educational background of OHS, no reports for work disease and work accident, no room and special funds for the OHS Unit, there is an OHS policy in writing and signed by the director, there is no risk management and no general OHS training for OHS members, incident investigation and corrective actions are good, review the implementation of OHSMS has been carried out but there is no follow-up of monitoring and evaluation of the OHS program. The conclusion, in general the application of OHSMS at Hospital X has not been going well, not all of them are in accordance with the existing regulations in PP. 50 of 2012.